A Himalayan triptych: narratives of traders, pilgrims and resistance in a landscape of movements. Issue 5 (20th October 2017) - Saul, Hayley; Waterton, Emma
ABSTRACT: For centuries, if not millennia, the north–south valley systems of Nepal's Himalayas have acted as a capillary network for communication, exchange, veneration, discriminating cultural difference and measuring out (early-)state power. One valley, in particular, the Kali Gandaki in Mustang, is a palimpsest overlaid with complex socialized and politicized movement. Drawing on the work of those affiliated with post-phenomenological thinking and using a mix of archaeological, archival and ethnographic data, this article disentangles and narrates five travels that emanate from this linear trail: the pilgrim, the salt trader, the resistance fighter, the explorer and the trekker. We start with the Buddhist pilgrim visiting the 2000-year-old Muktinath temple complex, for whom the route is a spiritual path. With each new vista unfolds a landscape of miracles and magic, the dusty road itself a medium for acquisition in the mysterious economy of merit. We then turn to the caravan traders who have plied their wares between gusty mountain passes and lowland jungle, exchanging Tibetan salt for Indian grains in a tradition of centuries. For them the trail is an exercise in risk management: when to move to fix the best price, navigating precipitous tracks, calculating how many animals to sell or to keep. Later this trade route would become a frontier zone when, in 1950, the Chinese People's Liberation Army invaded Tibet. In the decades that followed, a Tibetan guerilla-fighting unit led by a former monk, Bapa Yeshe, mounted assaults from Mustang over the border into Tibet before ultimately being abandoned by their American Central Intelligence Agency supporters. Theirs was a receding trail, looking out over a dissolving field of cultural memories, their movement a heaving final resistance against a red tide of Mao's intruders. Then there are the explorers – or nomadic cultural collectors – for whom the Annapurnas are a cornucopia of novelty. Each dusty step for them is further penetration into a landscape of alterity from which pieces of the other can be added to the collector's satchel. Finally, we come to present-day trekkers, who dream of pristine nature and for whom the trail leads to escape, clarity of mind, the past or the edge of security. As they retrace the same routes and pathways to which of these historical narratives, if any, do they bear witness?